Long-term participation tax rates - Charlotte Bartels (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2012)
Generous income support programs as provided by European welfare states have often been blamed to reduce work incentives for lower income classes and to increase durations of unemployment. Standard studies measure work incentives based on annual income concepts. This paper analyzes how work incentives inherent in the German tax-benefit system evolve when extending the time horizon to three years (long-term). Participation tax rates are computed for 3-year periods 1995-1997 and 2005-2007 to reveal potential effects of the labor market reforms between 2003 and 2005. Results show that long-term work incentives increased even more than short-term work incentives. Particularly for middle-income individuals, this is largely explained by the abolition of earnings-related unemployment assistance.
Keywords: H31; J65; 330; welfare; work incentives; unemployment; unemployment insurance; Sozialhilfe; Arbeitslosenversicherung; Hartz-Reform; Arbeitsangebot; Ökonomischer Anreiz; Deutschland